The Effect Of Planting And Volume Media Soaking Time Zpt Plant Seed On The Growth Beginning Of Cane ( Saccharum Officinarum L. ) System Bud Chip - Andriani Eko Prihatiningrum; Moch R Syarifuddin Fathony (Universitas Muhammadiyah Sidoarjo, 2017)
The study aims to determine the effect of interaction between the treatment effect of soaking tanamdan media volume ZPT against early seedling growth of sugarcane (Sac- charum officinarum L) system bud chip, green hause conducted at the University of Muhammadiyah Sidoarjo in November to January 2016. The study used randomized block design pola faktorial, consisting of two factors and three replications. The first fac- tor is the treatment of soaking ZPT consisting of 4 levels P0 (Without soaking ZPT), P1 (2 hours soaking ZPT), P2 (4 hours soaking ZPT), P3 (6 hours soaking ZPT), P4 (8 hours of soaking ZPT) , while the second factor is the volume of the growing media consisting of two kinds, V1 (80ml), V2 (200ml). Based on the results of analysis of variance study showed the combination treatment prolonged submersion tanamdan media volume ZPT no significant effect on the variable plant height, number of leaves, plant diameter, root length, root weight. Soaking ZPT on sugarcane crop seeds bud chip system with interval showed no real influence. the use of planting medium volume at the level V1 (80ml) and V2 (200) showed highly significant interaction. The use of volume media best planting with V2 (200ml) bud chip.